PENCANTUMAN KLAUSULA EKSONERASI DALAM PERJANJIAN SEBAGAI PERBUATAN MELAWAN HUKUM : (STUDI PUTUSAN NOMOR 930 K/PDT/2019) - Wilsin Lucianto (Veteran Law Review, 2023)
In Decision Number 898/Pdt.G/2016/PN.Jkt.Sel, ruled that the Plaintiff's lawsuit was vague and unacceptable because it had confused default with tort claims. Meanwhile, at the appeal level of the Decision, the Jakarta High Court through Decision Number 164/Pdt/2018/PT.DKI. which was upheld at the cassation level through Decision Number 930 K/PDT/2019, granted the cancellation of the exoneration clause on the grounds of default and not on the basis of tort. So it is interesting to discuss the inclusion of an exoneration clause in an agreement as a tort. To answer this, the research method used is juridical-normative legal research. The results of the study show that in applying for the cancellation of the exoneration clause through a tort lawsuit, in the posita section of the lawsuit the plaintiff must first describe the elements of a tort as follows: Unlawful Act, Fault, Loss and. Regarding the stipulation of the exoneration clause in the Agreement, the Panel of Judges in Decision Number 930 K/Pdt/2019 erred in their consideration that the exoneration clause that had been made in a standard manner by the Defendant which excluded or released the Defendant from claims and/or responsibilities was declared invalid. This is because if the Defendant did not want to accept the Plaintiff's claim, the Defendant should have made such a selection by requiring the Plaintiff to undergo a medical check-up first. Without a medical check-up, then when the Plaintiff suddenly became ill and the Defendant did not want to cover it, it can be interpreted that the Defendant did not act in good faith and committed an unlawful act rather than a default.